Electroacupuncture therapy and bone cancer pain relief: experimental study on analgesic mechanisms in rats - Li, Yanhua; Li, Fangfei; Xiao, Caizhi; Cao, Jie; Xia, Dongqin; Wu, Yongzhong (Frontiers in Pain Research, 2025)
BackgroundBone cancer pain is a common complication of advanced malignant tumors.Chemotherapeutic drugs, regardless of their origin or type, are often associated with various adverse effects such as gastrointestinal toxicity, immune suppression, and acquired drug resistance, which can compromise patients’ quality of life and treatment compliance. Electroacupuncture, known for its safety and analgesic effects, has been increasingly studied in bone cancer pain but the underlying mechanism is not fully understood.ObjectiveTo explore the mechanism of electroacupuncture in rats with bone cancer pain.MethodsForty-eight SD rats were divided into four groups: blank control, sham electroacupuncture, electroacupuncture-1, and electroacupuncture-2, with 12 rats in each group. Except the control group, rats were inoculated with cancer cells in the left tibia to induce bone cancer pain. The electroacupuncture groups received interventions starting on the 6th day after modeling. Mechanical pain sensitivity (PWT) and thermal pain sensitivity (PWL) were assessed, and the expression of phosphorylated glycogen synthase kinase-3 (p-GSK-3) and glial fibrillary acidic protein (GFAP) in the spinal cord were analyzed. HE staining was used to observe tibial pathological changes.ResultsFrom the 6th day, PWT and PWL were significantly reduced in the control group compared to the sham group (P < 0.05). Electroacupuncture-1 significantly increased PWT and PWL compared to the sham group (P < 0.05), while no significant changes were observed in electroacupuncture-2 compared to the control. On day 12, spinal p-GSK-3 levels were significantly lower and GFAP levels significantly higher in the model and control groups compared to the electroacupuncture-1 group (P < 0.05). The electroacupuncture-2 group showed no significant changes. Inflammatory cytokines IL-1, IL-6, and TNF-α were significantly elevated in the model group compared to the control (P < 0.05), but significantly reduced in the electroacupuncture-1 group (P < 0.05). HE staining showed cancer cell infiltration and bone tissue damage in the sham and electroacupuncture groups.ConclusionElectroacupuncture significantly reduced the pain threshold in rats with bone cancer pain. This effect is likely due to the down-regulation of GSK-3 activity, inhibition of astrocyte activation, and reduction in inflammatory responses.